SPATIO TEMPORAL ANALYSIS TO INDICATIONS OF URBAN HEAT ISLAND IN JAMBI CITY - Kurnianingsih Kurnianingsih; Bangun Muljo Sukojo; Siswanto Siswanto; Muhammad Reza Ferdiansyah (GeoEco)
The high population growth in Jambi City has resulted in land conversion from vegetation to built-up land and settlements, and the use of motorized vehicles has increased the release of carbon emissions which also increase air temperature in Jambi City. To better understand and identify the urban heat island (UHI) phenomenon, spatial and temporal analysis is needed using remote sensing data with a long series from 2000 to 2024. This study aims to examine the intensity of UHI in Jambi City by measuring the surface urban heat island index (SUHII) and the urban thermal field variance index (UTFVI) by utilizing the Land Surface Temperature (LST) and Enhanced Vegetation Index (EVI) products. Correlation analysis shows that Jambi City is an area with the highest LST and the lowest EVI index compared to the surrounding areas. The SUHI intensity in Jambi City has a positive value between 0.2 - 2.5 °C. Meanwhile, the intensity of AUHI between urban and suburban areas ranges from -0.2 - 0.3 °C during the day and -0.1 - 0.1 °C at night. The UTFVI index is in the range of 0.01 - 0.07. Although the intensity of SUHI and AUHI is not too large and the decrease in EVI value can be an indicator of UHI in Jambi City. The correlation test between LST and air temperature of the station has a sufficient category except for the correlation between LST and air temperature of the Kerinci Meteorological Station which has a very weak category.